Contemporary problems in the law of contract - Edelman, J; Goudkamp, J; Degeling, S (Australian Bar Association, 2015)
On 18 and 19 December 2015 UNSW Law will host a conference entitled Contracts in Commercial Law. Full details regarding the conference are available at the conference website http://www.contracts.law.unsw.edu.au/ and can be obtained by sending an email to: contracts@unsw.edu.au. The conference, which is sponsored by Allens and Linklaters, will consider timeless and emerging problems in the law of contract. It will bring together judges, academics, and practitioners who are leading experts on contract law in order to explain and debate these problems. As we discuss below, the speakers include some of the most distinguished legal thinkers from Australia, Canada, United Kingdom, New Zealand and Singapore. The fact that the conference will see judges, academics and practitioners working together in the quest to resolve today's most pressing problems in the law of contract merits emphasis. The days that saw a sharp separation between, in particular, the work of judges and academics, have largely faded from memory. Whereas in the past judges would, for example, rarely cite academic works, many judicial officers in the present day are acutely interested in and depend heavily upon insights from academia. It is commonplace for litigants to put before judges academic materials in support of their arguments and, in turn, for judges to make extensive recourse to these materials in writing their opinions. Consistently with the modern approach, the conference avoids historical divisions between the judiciary, the academy and the practising profession.